2013
DOI: 10.1186/1472-6882-13-262
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of xanthones from Calophyllum brasiliense: prevention of oxidative damage induced by FeSO4

Abstract: BackgroundReactive oxygen species (ROS) are important mediators in a number of degenerative diseases. Oxidative stress refers to the imbalance between the production of ROS and the ability to scavenge these species through endogenous antioxidant systems. Since antioxidants can inhibit oxidative processes, it becomes relevant to describe natural compounds with antioxidant properties which may be designed as therapies to decrease oxidative damage and stimulate endogenous cytoprotective systems. The present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 47 publications
(55 reference statements)
1
14
1
2
Order By: Relevance
“…Quercetin and daidzein have been detected by Franchi Jr. et al (2012) in Brazilian red propolis from Alagoas State. Others studies also detected antioxidant activity of the flavonoids isoliquiritigenin (Ondrias et al, 1997) and pinobanksin (Blanco-Ayala et al, 2013) in red propolis.…”
Section: Discussionmentioning
confidence: 90%
“…Quercetin and daidzein have been detected by Franchi Jr. et al (2012) in Brazilian red propolis from Alagoas State. Others studies also detected antioxidant activity of the flavonoids isoliquiritigenin (Ondrias et al, 1997) and pinobanksin (Blanco-Ayala et al, 2013) in red propolis.…”
Section: Discussionmentioning
confidence: 90%
“…Quercetin and daidzein have been detected by Franchi Jr. et al [ 2 ] in Brazilian red propolis from Alagoas State. Others studies also detected antioxidant activity of the flavonoids isoliquiritigenin [ 47 ] and pinobanksin [ 48 ] in red propolis.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which oral ferrous sulfate may have caused sulfhaemoglobin in our patient is unclear but the two characteristics named above are present in ferrous sulfate. First, it provides a source for sulfur and second, literature has shown that it can cause oxidative damage in toxic levels 9. It remains unclear however, whether the oxidation could occur in normal ferrous sulfate levels or whether the patient actually had toxic levels at some point.…”
Section: Discussionmentioning
confidence: 99%